2015
DOI: 10.1371/journal.pone.0140039
|View full text |Cite
|
Sign up to set email alerts
|

Improved Production Efficiency of Virus-Like Particles by the Baculovirus Expression Vector System

Abstract: Vaccines based on virus-like particles (VLPs) have proven effective in humans and animals. In this regard, the baculovirus expression vector system (BEVS) is one of the technologies of choice to generate such highly immunogenic vaccines. The extended use of these vaccines for human and animal populations is constrained because of high production costs, therefore a significant improvement in productivity is crucial to ensure their commercial viability. Here we describe the use of the previously described baculo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…All these vaccines are directed against the PCV2a subtype. Although an improvement in the expression of self-contained Cap protein in insect cells has been achieved [ 73 , 74 ], in our hands, the production and isolation of VarC chimeric structures carrying the fused Cap protein of PCV2b subtype was more efficient and easy. Another advantage of the VarC chimeric vaccine is that it represents a so-called DIVA (differentiating infected from vaccinated animals) vaccine, which also induces an immune response that differs from the response induced by natural infection, in this case, antibodies against the mouse polyoma VP1 protein.…”
Section: Resultsmentioning
confidence: 99%
“…All these vaccines are directed against the PCV2a subtype. Although an improvement in the expression of self-contained Cap protein in insect cells has been achieved [ 73 , 74 ], in our hands, the production and isolation of VarC chimeric structures carrying the fused Cap protein of PCV2b subtype was more efficient and easy. Another advantage of the VarC chimeric vaccine is that it represents a so-called DIVA (differentiating infected from vaccinated animals) vaccine, which also induces an immune response that differs from the response induced by natural infection, in this case, antibodies against the mouse polyoma VP1 protein.…”
Section: Resultsmentioning
confidence: 99%
“…As compared to monomeric antigens, nanoparticle vaccines have been demonstrated to induce significantly stronger humoral responses to various targets including HIV, influenza, RSV, and malaria (126)(127)(128)(129)(130). However, assembly of these nano-vaccines is technologically cumbersome and costly with the conventional techniques (131). Xu et al recently demonstrated that DNA/EP can enable direct de novo assembly of nanoparticle vaccines in the hosts to bypass such complex production processes (27,132).…”
Section: Dna Launched Nano-vaccinesmentioning
confidence: 99%
“…Synthetic engineering of baculovirus vectors using combinations of transcriptional or translational elements can increase yield in this system (Gómez‐Sebastián, López‐Vidal, & Escribano, ; Liu, Zhang, et al, 2015). Similarly, a synthetically designed expression cassette, containing rearranged genetic regulatory elements, transcription factors IE1 and IE0 and a transcription enhancer sequence linked to differential promoters, increased both expression and cell viability of porcine circovirus VLPs and rabbit hemorrhagic disease VLPs in IC‐BEVS (López‐Vidal et al, ).…”
Section: Considerations For Vlp Productionmentioning
confidence: 99%